Analyzing the Total Resistance and Wave Pattern of Purse Seine Vessels with Photovoltaic-Powered - Naryanto, Rizqi Fitri; Bahatmaka, Aldias; Wibowo, Muhammad Yusuf; Ghyferi, Andi Abdullah; Fahmi, Fiqri Fadillah; Hyoung Cho, Joung (Rekayasa, 2024)
With 64.97% of its territory consisting of sea, Indonesia is one of the world's largest maritime nations and produces approximately 8.02 million tons of fish annually. Traditional fishing vessels play a crucial role in supporting livelihoods, yet their design is often based on hereditary methods rather than hydrodynamic optimization. This study uses catamaran hull forms as a design reference to analyze the total resistance and wave patterns of purse seine vessels with photovoltaic-powered systems. Computational methods are employed to predict vessel performance efficiently. The resistance analysis applies the Slender Body approach and Savitsky's mathematical model, supported by comparative studies for validation. Particular attention is given to the influence of chine configurations on resistance characteristics and wave formation. Results indicate that the addition of chines increases the Froude number and contributes to reducing total resistance. Among the variations, single chine geometry demonstrates the lowest resistance, making it the most efficient configuration for catamaran fishing vessels. While chine modifications affect the wave pattern, the hull maintains a relatively clean wake distribution. These findings highlight the potential for improving vessel design through careful chine geometry optimization combined with computational modeling. The study underscores the importance of modern hydrodynamic analysis in advancing traditional fishing vessels toward higher efficiency and sustainability. Future research is recommended to incorporate more advanced computational approaches, such as Computational Fluid Dynamics (CFD), examine water-hull interactions and enhance vessel performance under operational conditions.